Assessing the influence of online teaching and learning hurdles on job performance of university lecturers in Selangor - Yahya , Nur Fauzana; Johari , Fatin Fasihah; Hashim , Hanita (International Journal of Accounting, Finance and Business, 2025)
This study examines the factors that influence lecturers' job performance in the context of online learning in private higher education institutions in Selangor. Using a sample of 153 lecturers selected through convenience sampling, the study examines the impact of emotion, internet accessibility, and the learning environment on job performance. Quantitative methods, including reliability testing, descriptive statistics, correlation, and regression analysis, were employed to analyze the data. The findings reveal strong positive relationships between job performance and the independent variables. Regression analysis indicates that emotion (β = 0.329, p = 0.001) and internet accessibility (β = 0.410, p = 0.001) are the most significant predictors of job performance, with the learning environment (β = 0.205, p = 0.021) also contributing positively. The model explains 60% of the variance in job performance, demonstrating the collective importance of these factors. These results highlight the critical roles of emotional engagement, reliable internet access, and a conducive learning environment in enhancing lecturers’ performance in online teaching. The study underscores the importance of institutions prioritizing technological infrastructure, emotional support, and supportive environments to optimize job performance. Recommendations for future research include exploring additional factors such as institutional support, workload, and training to provide a more comprehensive understanding of job performance in online learning settings.